ENVIRONMENT VS TRADE-STUDY ON ECO-LABELLING - Respati, Yossi Niken (Bina Hukum Lingkungan, 2019)
In global era where trade liberalization requires free mobilization of goods and services as well as investment between countries with eradication of technical barriers on trade, there is a question if free trade can accommodate on the same level of environmental interests, particularly for developing countries which face huge economic gap with the developed countries. Most of developing countries dominate global exports in goods. It is an advantage for the countries to derive state income but at the same time they are also exposed to the big environmental damage potentials because of the trade in natural resources. Correlation between economic activities (trade) and environmental protection has been drawing global attention, as environmental issues usually emerges from the economic activities and becomes a victim of it as well. This paper will describe the eco-label and its implementation in Indonesia, and the role of eco-label through environmental and international trade. In conclusion, ecolabelling program have the potential to be misused as technical barriers to trade and provided developing countries must be concern with the market access of their exports into developed countries and most importantly, the vast difference between the environmental concerns of various countries should be recognized then the use of eco-labels for constraining potentially hazardous behavior to environment inevitably get constrained.